Continuous Theta-Burst Stimulation Intensity Dependently Facilitates Motor-Evoked Potentials Following Focal Electrical Stimulation of the Rat Motor Cortex - Fujiki, Minoru; Kawasaki, Yukari; Fudaba, Hirotaka (Frontiers in Neural Circuits, 2020)
Although theta burst stimulation (TBS) is known to differentially modify motor cortical excitability according to stimulus conditions in humans, whether similar effects can be seen in animals, in particular rats, remains to be defined. Given the importance of experimental rat models for humans, this study explored this stimulation paradigm in rats. Specifically, this study aimed to explore corticospinal excitability after TBS in anesthetized animals to confirm its comparability with human results. Both inhibition-facilitation configurations using paired electrical stimulation protocols and the effects of the TBS paradigm on motor-evoked potentials (MEPs) in rat descending motor pathways were assessed. Paired-stimulation MEPs showed inhibition (interstimulus interval [ISI]: 3 ms) and facilitation (11 ms) patterns under medetomidine/midazolam/butorphanol (MMB) anesthesia. Furthermore, while ketamine and xylazine (K/X) anesthesia completely blocked facilitation at 11-ms ISI, inhibition at a 3-ms ISI was preserved. Continuous and intermittent TBS strongly facilitated MEPs depending on stimulus intensity, persisting for up to 25 min under both MMB and K/X anesthesia. These findings are similar to the intracortical inhibition and facilitation observed in the human motor cortex using paired-pulse magnetic stimulation, particularly the glutamate-mediated facilitation phase. However, different TBS facilitatory mechanisms occur in the rat motor cortex. These different TBS facilitatory mechanisms affect the comparability and interpretations of TBS between rat and human models.